Chronotype, cognitive outcomes, and neural dynamics: recent evidence and potential mechanisms with implications for perioperative period - Liu, Ying; Liu, Qijing; Gao, Boxiong; Fu, Qian; Li, Fang; Ma, Yuhu; Liu, Yatao (Frontiers in Neuroscience, 2025)
Circadian rhythm plays a fundamental role in regulating biological functions, including sleep–wake preferences, body temperature, hormone secretion, food intake, cognitive function and physical performance. The sleep chronotype, as part of the circadian rhythm, usually refers to an individual’s subjective preference for their own sleep–wake cycle. Because of the differences in brain microstructure and resting-state connections between different sleep chronotype, it may lead to differences in individual cognitive function. Concurrently, the pathophysiological mechanisms underlying the association between perioperative circadian misalignment and postoperative cognitive dysfunction (POCD), as well as targeted therapeutic strategies, have garnered increasing attention in recent research. Chronotype exerts regulatory effects on cognitive function via circadian rhythm modulation, neuroinflammatory cascades, and metabolic homeostasis. Perioperative alterations in sleep architecture—including diminished slow-wave sleep (SWS) and circadian desynchronization—may potentiate cognitive deficits and exacerbating neuroinflammation-mediated neuronal apoptosis. This review mainly focuses on the relationship between sleep chronotype and cognitive function as well as perioperative sleep chronotype changes, providing the latest evidence of relevant studies of domestic and foreign. In addition, different sleep patterns and postoperative cognitive dysfunction are prospected, which provides a new direction for exploring the different mechanisms of postoperative cognitive dysfunction in the future.